Rzymski okres biografii Stanisława Poniatowskiego w krzywym zwierciadle Giuseppego Gioachina Bellego - Mangiapelo, Alessio (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
In his book I Poniatowski e Roma (1971), Andrea Busiri Vici recalled a meeting between the young Giuseppe Gioachino Belli (1791–1863), who would later become a master of Italian dialect poetry, and the older Stanisław Poniatowski (1754–1833), nephew of King Stanisław August. The two men were connected by both professional and personal ties. Their relationship came to an end due to a court intrigue involving suspicions of an affair between Belli and Cassandra Luci, the prince’s wife. Busiri Vici described the matter in detail, drawing on numerous literary sources. This article aims to reconstruct that relationship from the perspective of the Italian poet by way of literary scholarship tools such as textual interpretation, translation studies, literary history, and comparative literature.